Analisis Iklim Komunikasi dalam Menumbuhkan Berbagi Pengetahuan di Perpustakaan Daniel S. Lev - Anjani, Virgia; Fauziah, Kiki (Jurnal Ilmu Informasi, Perpustakaan, dan Kearsipan, 2021)
This study analyzes the factors of organizational communication climate in fostering knowledge sharing in Daniel S. Lev library which is a special library of law and political literature. This study was examined using the dimensions of organizational communication climate that was coined by Charles W. Redding, wherein the concept there are five values; supportiveness, participation in decision making, trust and reliability, openness, and high-performance goals. This is qualitative research using the case study method. The informants of this research are the Head of the Library and all library staff. The results of this study indicate that the five values of the Redding communication climate dimension contribute to fostering knowledge sharing activities in the Daniel S. Lev library. Knowledge sharing activities that have grown include weekly meetings, reports, activity presentations, publications, mentoring, and sharing while working. The value of openness and the value of high-performance goals become the dominant values.